Religious Titles and Positions In State Administration and The Role Of Religious Representatives In Them - Shirinov Sardor (Indonesian Journal Publisher, 2025)
This study analyzes the role of religious titles and positions in state administration and their impact on socio-political processes in the Central Asian khanates. During the Shaybanids, Ashtarkhanids, and Mangids, the relationship of religious officials with political power, the functions of positions such as sheikh-ul-Islam, qozikalon, sadr, mufti and their status in society are studied based on historical sources. The participation of religious leaders in the judiciary, educational institutions, and state administration is also analyzed, with special attention paid to changes in the role of religious titles in society during the Bukhara Emirate. The study is conducted on the basis of historical sources such as Muhammad Sayyid Baljuvani's